The Effect of Training and Work Environment on Employee Performance with Job Satisfaction as Moderating Variable at PT Karsa Mulia Sejahtera Balikpapan - Muhammad Fernanda Fadilah; Nurul Asfiah; Kenny Roz (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
The aim of this study is to determine if training and workplace environment have an impact on employee performance with job satisfaction acting as a moderating variable. This type of study employs a quantified approach and a 40-person sample size. Information was gathered by handing out surveys (primary data). The statistics in this research are examined using path analysis. According to research findings, training has a positive but not statistically significant effect on employee performance, job satisfaction has a positive and statistically significant effect on employee performance, and work environment has a positive and statistically significant effect on employee performance. However, job satisfaction is unable to moderate either of these effects on employee performance.